Retailers and Consumers: The pass-through of import price changes - Eike Berner; Laura Birg; Dominik Boddin (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
In this paper, we estimate pass-through rates of import price changes to retail prices across retailers and consumers for apparel purchases in Germany for the period of 2000 to 2007. We find that high-price retailers do not pass through changes in the import price. Pass-through rates for low-price retailers are 53% within 3 months. Consequently, pass-through rates for low-income households are 58%, significantly larger than those for high-income households. We then present one possible explanation for these observations in a theoretical model with endogenous vertical product differentiation due to bundling an ex-ante homogeneous import good with services. Following an import price change, retailers who sell a cheaper unbundled product change prices to a greater extent than retailers who sell a higher-priced bundle of product and service.
Keywords: D12; D31; F10; 330; import prices; pass-through; retailers; households